1958
DOI: 10.1084/jem.107.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pathogenesis of Fever

Abstract: Evidence has been previously presented that an endogenous pyrogen is demonstrable in the circulation of rabbits with fever caused by the intravenous injection of typhoid vaccine (1, 2). The endogenous factor is readily differentiated from the pyrogenic component of the vaccine and reaches a maximum concentration well after the latter has been cleared from the blood stream. Its presence in the circulation is closely correlated with the fever. These observations have recently been confirmed in analogous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1958
1958
1974
1974

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 14 publications
(19 reference statements)
1
22
1
Order By: Relevance
“…The basic procedures used (a) in eliminating extraneous pyrogens from reagents and glassware, (b) in assaying the activity of endogenous pyrogen by intravenous injection of rabbits, and (¢) in measuring the febrile response to pyrogen in arbitrary fever index units have been described in previous publications (9,10). All of the fever indices recorded in this study were calculated from 2 hour fever curves, since the febrile response to leucocytic pyrogen rarely extends beyond the 2nd hour, except when massive doses of pyrogen are employed (13).…”
Section: Methodsmentioning
confidence: 99%
“…The basic procedures used (a) in eliminating extraneous pyrogens from reagents and glassware, (b) in assaying the activity of endogenous pyrogen by intravenous injection of rabbits, and (¢) in measuring the febrile response to pyrogen in arbitrary fever index units have been described in previous publications (9,10). All of the fever indices recorded in this study were calculated from 2 hour fever curves, since the febrile response to leucocytic pyrogen rarely extends beyond the 2nd hour, except when massive doses of pyrogen are employed (13).…”
Section: Methodsmentioning
confidence: 99%
“…The method finally adopted revealed that endogenous pyrogen, as it exists both in leucocytic exudates (3,18) and in 2 hour serum (5, 6) causes a more rapid and a more pronounced fever when introduced ~a the carotid artery than when injected intravenously. The exogenous pyrogen in 5 minute serum (5, 6), on the other hand, caused a relatively slow response which was uninfluenced by the route of injection.…”
Section: Discussionmentioning
confidence: 99%
“…The approximate position of an intracarotid catheter, however, can be deter-I The method of calculatiag the fever indices was the same as in the preceding study (18) except that a cut-off point of 240 minutes was arbitrarily used because of the consistently longer responses produced by exogenous pyrogen.…”
Section: Exploratory Experiments To Determine Optlmal Position Of Intmentioning
confidence: 99%
See 2 more Smart Citations